PENGARUH HARGA, STRATEGI PROMOSI DAN TEMPAT TERHADAP KEPUTUSAN PEMBELIAN AYAM POTONG DI PASAR KERTOSONO - Mahardika, Sena (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of price, promotion strategy, and place either partially or simultaneously on purchasing decisions of broiler chicken. This research uses a quantitative approach and is casual research. The population in this study are all consumers of broiler chicken whose number is unlimited or uncountable. The sample was determined as many as 40 respondents who were taken using an accidental sampling technique. The data collection technique using questionnaire and data analysis used in this study is multiple linear regression analysis. The results showed that price, promotion strategy and place had a significant effect on purchasing decisions, while simultaneously price, promotion strategy and place had a significant effect on purchasing decisions of broiler chicken.